Bangladesh, national culture, and heritage : an introductory reader - Ahmed, A. F. Salahuddin, edt. ...[et al (Dhaka : Independent University, Bangladesh, 2022)
Contributed articles on history and civilization of Bangladesh in 19th and 20th century.
Includes bibliographical references and index.
Keywords: Bangladesh -- History -- 19th century